Determination of ginsenosides by Bacillus polymyxa conversion and evaluation on pharmacological activities of the conversion products. Issue 6 (June 2015) - Ji, Qing; Gao, Yugang; Zhao, Yan; He, Zhongmei; Zang, Pu; Zhu, Hongyan; Yang, He; Li, Xue; Zhang, Lianxue
Graphical abstract: Highlights: The Bacillus polymyxa is used to transform ginsenosides for the first time. 12 ginsenosides of transformation products were analyzed. The transformation products have the activities of anti-fatigue, immunization, antitumor. Abstract: Bacillus polymyxa was used to transform ginseng for the first time. Furthermore, the pharmacological activities of the conversion products were evaluated. Twelve kinds of ginsenosides of conversion products were detected by high performance liquid chromatography (HPLC). The results showed that the contents of ginsenosides Rb3, Re, Rd, CK, protopanaxadiol were significantly increased. Moreover, the conversion products had anti-fatigue, immune enhancement, and antitumor activities by the certification of pharmacodynamics experiments. The study provides a theoretical basis and reference for future research on microbial transformation of ginseng.